Toward the construction of 3D dipeptide-metal frameworks - Seyedali Emami (2014)
Single amino acids have been vastly used to generate metal−biomolecule frameworks. Three-dimensional (3D) frameworks based on di- and tripeptide frameworks remain nevertheless quite scarce. We report the preparation of unique 3D dipeptide−metal frameworks in which both amino acid residues participate in metal coordination and in the construction of the networks.